Aspectos clínicos, sintomas persistentes, funcionalidade e qualidade de vida dos pacientes, em média, 24 meses após diagnóstico da COVID-19 - SALGADO, Marcos Moreno (2024)
Introduction: Patients who have been affected by SARS-CoV-2 may experience sequelae and symptoms after the acute phase of the disease, such as dyspnea, fatigue, muscle weakness, abnormalities in lung function and decreased quality of life scores. Objective: Evaluate the clinical, functional aspects and quality of life in individuals after recovery from COVID-19. Materials and Methods: This is a descriptive observational study, carried out in a post-COVID-19 reference center in São Luís - MA. The study sample consisted of 43 individuals of both sexes, mean age of 55±12.3 years. Data collection was carried out using manovacuometry, Fatigue Assessment Scale (FAS), Post-COVID-19 Functional Scale (PCFS), EuroQol-5D quality of life questionnaire (EQ-5D-5L) and anthropometry. Results: Our sample showed a prevalence of women (81.4%), with a mean age of 55 ±12.3 years, 93.0% complained of tiredness and fatigue. Women had a higher percentage of normal MIP (60.5%) and MEP with moderate changes (36.8%) and men, in the majority, had normal MIP (50.0%) and Severe MEP (75.0%). 51.2% had moderate functional limitation and 48.% had fatigue. An average of 60 was observed on the EQ-5D-5L visual analogue scale, high cardiovascular risk based on WHR (46.5%), 16.3% sarcopenic and 83.7% non-sarcopenic. Furthermore, significant associations were observed between anthropometric variables (p<0.05). Furthermore, when performing unsupervised machine learning analyses, we observed that higher MIP and MEP values seem to be related to lower levels of fatigue and sarcopenia. Furthermore, the main components present in the multivariate analysis were: waist, hip, calf circumference and MIP. Conclusion: Our data demonstrate that changes in anthropometric dimensions seemed to have a greater negative influence on individuals' functionality and quality of life. Furthermore, fatigue, joint pain and dyspnea were evidenced as the main persistent symptoms even after 24 months of recovery from COVID-19.